In silico μελέτη της αντιδιαβητικής δράσης μεσογειακών φυτών με την χρήση της πλατφόρμας DIA-DB - Κωνσταντίνου, Αθηνά (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας, και Επιστήμης Τροφίμων, 2021)
Natural products have been widely used in traditional medicine to prevent and treat diabetes mellitus. In vivo and clinical studies also highlight the possible antidiabetic effects of medicinal plants. The Mediterranean flora is considered as a rich source of compounds with potential anti-diabetic activity. The aim of this dissertation was to evaluate and understand the antidiabetic effects of Mediterranean medicinal plants as well as to pinpoint new natural antidiabetic compounds by the employment of an in-silico approach. At the first step, a literature review for Mediterranean plants with antidiabetic properties was conducted and then the most active plants were chosen. Subsequently, the bioactive composition of each plant was found and the most abundant compounds were classified into phenolic acids, flavonoids and terpenes. Finally, the selected compounds were screened with the DIA-DB web server against 18 known diabetes drug targets. Furthermore, the structures of the most active compounds were compared the structures of 191 known drugs for diabetes. Results showed that phenolic compounds had high docking scores with protein targets suggesting a strong antidiabetic activity. Flavonoids as hesperidin, rutin, apigenin and luteolin are found as the most promising antidiabetic compounds. On contrary, docking scores phenolic acids and terpenes demonstrated weak possible antidiabetic effects. Phenolic compounds mainly docked with targets 2WR6_rec, 4K1L_rec, 3G5E_rec, 4A5S_rec, 2FVJ_rec. Furthermore, the results showed that the structures of active flavonoids had a high correlation with the structures of 191 well-known drugs for diabetes. In conclusion, the present study demonstrates that the antidiabetic effects of Mediterranean plants mainly contributed to the flavonoids. Further in vivo and clinical studies are required to establish their potency.
Keywords: διαβήτης; φλαβανοειδή; φαινολικά οξέα; φαρμακευτικά φυτά; μηχανισμοί δράσης